Odpowiedź :
Odpowiedź:
x = 0 lub x = - 1 lub x = - 3 lub x = 3
Iloczyn jest równy 0.
Szczegółowe wyjaśnienie:
[tex]2x(x^{2}-9)(x+1) = 0 \ \ \ |:2\\\\x(x^{2}-3^{2})(x+1) = 0[/tex]
Korzystamy ze wzoru skróconego mnożenia:
(a + b)(a - b) = a² - b²
[tex]x(x+3)(x-3)(x+1) = 0\\\\x = 0 \ \vee \ x+3 = 0 \ \vee \ x-3 = 0 \ \vee \ x+1 = 0\\\\x = 0 \ \vee \ x = -3 \ \vee \ x = 3 \ \vee \ x = -1\\\\Iloczyn = 0\cdot(-3)\cdot3\cdot(-1) = \boxed{0}[/tex]
Wyjaśnienie:
Jeżeli jednym z czynników jest 0, to iloczyn jest równy 0.